Radiation-Induced Bystander Effect is Mediated by Mitochondrial DNA in Exosome-Like Vesicles - Kentaro Ariyoshi (Nature Portfolio, 2019)
Abstract Exosome-like vesicles (ELV) are involved in mediating radiation-induced bystander effect (RIBE). Here, we used ELV from control cell conditioned medium (CCCM) and from 4 Gy of X-ray irradiated cell conditioned medium (ICCM), which has been used to culture normal human fibroblast cells to examine the possibility of ELV mediating RIBE signals. We investigated whether ELV from 4 Gy irradiated mouse serum mediate RIBE signals. Induction of DNA damage was observed in cells that were treated with ICCM ELV and ELV from 4 Gy irradiated mouse serum. In addition, we treated CCCM ELV and ICCM ELV with RNases, DNases, and proteinases to determine which component of ELV is responsible for RIBE. Induction of DNA damage by ICCM ELV was not observed after treatment with DNases. After treatment, DNA damages were not induced in CCCM ELV or ICCM ELV from mitochondria depleted (ρ0) normal human fibroblast cells. Further, we found significant increase in mitochondrial DNA (mtDNA) in ICCM ELV and ELV from 4 Gy irradiated mouse serum. ELV carrying amplified mtDNA (ND1, ND5) induced DNA damage in treated cells. These data suggest that the secretion of mtDNA through exosomes is involved in mediating RIBE signals.